The study of Internet Addiction With Depression, Anxiety and Social Isolation - Abdul Ghani, Wan Soraya Wan; Ramlee, Nureliyana; Ramli, Nurakmal; Zamri, Hafizi; Ghazali, Ayu Rohaidah (Advances in Business Research International Journal, 2024)
The internet is an instrument that is utilized as a fundamental part of daily life throughout the world. Undoubtedly, the internet is a revolution in information technology. However, internet addiction is becoming a problem among some users as the usage of the internet is growing rapidly each year. Therefore, this study aimed to determine the relationship between internet addiction and developing of anxiety, depression and social isolation. Based on the sample size, 61 respondents were used to participate in this study. Census technique was applied in the distribution of the questionnaire. The results shown that there is a positive relationship between internet addiction towards developing anxiety, depression and social isolation. However, new studies are required to document the efficacy treatment of for the subjected issue. Further discussion on the results are shared in this paper.